Preliminary and criminal proceedings against legal persons and associations of persons  on the legal situation in Germany - Sackreuther, Kai (European Integration Studies, 2023)
This article is based on a lecture given on 29 November 2021 at the II Conference of the Universities of Heidelberg and Miskolc within the framework of the Humboldt Institute Partner Project "Systematising criminal responsibility of and in corporations". It presents the procedural law applicable in Germany and the intended changes within the framework of the so-called Association Sanctions Act, dealing with questions of conducting internal investigations in the company and the associated obligations to submit documents and to disclose other circumstances relevant to criminal proceedings. The question of whether the prohibition of self-incrimination is to be recognised for legal persons and to what extent internal investigations can constitute grounds for a mitigation of sanctions is also examined.